How to twist a dragon's tale - Cowell, Cressida (How to train your dragon ;, 2008)
Someone has stolen the Fire Egg. Now the volcano on Volcano Island is active and the tremors are hatching the eggs of the exterminator dragons! Can Hiccup return the Fire Egg to the volcano, stop the volcano from erupting, and save the Tribes from being wiped out by the terrible sword-claws of the Exterminators.